Quaternion-Based Attitude Control System Design of Single and Cooperative Spacecrafts: Boundedness of Solution Approach. (19th May 2014) - Septanto, Harry; Bambang, Riyanto T.; Syaichu-Rohman, Arief; Eko Poetro, Ridanto; Ravi Ibrahim, Adrianto
Abstract : It is well known that single equilibrium orientation point in matrix rotation is represented by two equilibrium points in quaternion. This fact would imply nonefficient control effort as well as problem in guaranteeing stability of the two equilibrium points in quaternion. This paper presents a solution to design quaternion-based spacecraft attitude control system whose saturation element is in its control law such that those problems are overcome. The proposed feature of methodology is the consideration on boundedness of solution in the control system design even in the presence of unknown external disturbance. The same methodology is also used to design cooperative spacecrafts attitude control system. Through the proposed method, the most relaxed information-state topology requirement is obtained, that is, the directed graph that contains a directed spanning tree. Some numerical simulations demonstrate effectiveness of the proposed feature of methodology.